Cardiac imaging at 7 tesla: Single‐ and two‐spoke radiofrequency pulse design with 16‐channel parallel excitation. Issue 5 (10th September 2013) - Schmitter, Sebastian; DelaBarre, Lance; Wu, Xiaoping; Greiser, Andreas; Wang, Dingxin; Auerbach, Edward J.; Vaughan, J. Thomas; Uğurbil, Kâmil; Van de, Pierre‐François
<x xml:space="preserve">Abstract</x> Purpose Higher signal to noise ratio (SNR) and improved contrast have been demonstrated at ultra‐high magnetic fields (≥7 Tesla [T]) in multiple targets, often with multi‐channel transmit methods to address the deleterious impact on tissue contrast due to spatial variations in B1+ profiles. When imaging the heart at 7T, however, respiratory and cardiac motion, as well as B0 inhomogeneity, greatly increase the methodological challenge. In this study we compare two‐spoke parallel transmit (pTX) RF pulses with static B1+ shimming in cardiac imaging at 7T. Methods Using a 16‐channel pTX system, slice‐selective two‐spoke pTX pulses and static B1+ shimming were applied in cardiac CINE imaging. B1+ and B0 mapping required modified cardiac triggered sequences. Excitation homogeneity and RF energy were compared in different imaging orientations. Results Two‐spoke pulses provide higher excitation homogeneity than B1+ shimming, especially in the more challenging posterior region of the heart. The peak value of channel‐wise RF energy was reduced, allowing for a higher flip angle, hence increased tissue contrast. Image quality with two‐spoke excitation proved to be stable throughout the entire cardiac cycle. Conclusion Two‐spoke pTX excitation has been successfully demonstrated in the human heart at 7T, with improved image quality and reduced RF pulse energy when compared with B1+ shimming. Magn Reson Med 70:1210–1219, 2013. © 2013 Wiley Periodicals, Inc.